Online ultrasonic terminal for measuring pig backfat thickness - Zhang, Ganghong; Gao, Wanlin; Tao, Sha; Yu, Lina; Zhang, Guofeng; Luo, Xuan (International Journal of Agricultural and Biological Engineering, 2018)
The measurement of pig backfat thickness (PBFT) has to stand up to challenges with the reliability, accuracy, and convenience. Acquiring PBFT timely and precisely from a finite distance is extremely necessary to improve the process of pig production and implement effective management. In an attempt to alleviate these problems, an online handheld terminal was designed with a new method based on ultrasonic technology for measuring PBFT during the process of pig breeding, which can overcome the difficulties encountered in other destructive means. The terminal comprised three main components: a main microcontroller unit (MCU) to measure PBFT, a RFID module to identify each pig and send data (e.g. identity, measurement time and PBFT) to a server via wireless transmission module, and an ultrasonic transducer to drive and receive signals between them. A measurement error within 0-1 mm was acquired through testing three groups of samples. Results indicated that this handheld terminal had a required accuracy and proved that the ultrasonic wave processing method can be deployed in a mobile terminal for PBFT measurement. It also provided a feasible nondestructive alternative to measure PBFT. Associated with information management software platform, this method may ultimately help pig production farmers measure the PBFT accurately and conveniently, and improve the pig production efficiency.Keywords: pig backfat thickness, nondestructive measurement, ultrasonic technology, online terminal, pig productionDOI: 10.25165/j.ijabe.20181102.3278Citation: Zhang G H, Gao W L, Tao S, Yu L N, Zhang G F, Luo X. Online ultrasonic terminal for measuring pig backfat thickness. Int J Agric & Biol Eng, 2018; 11(2): 190–195.